2011
DOI: 10.1631/jzus.b1000371
|View full text |Cite
|
Sign up to set email alerts
|

A recessive gene controlling male sterility sensitive to short daylength/low temperature in wheat (Triticum aestivum L.)

Abstract: Utilization of a two-line breeding system via photoperiod-thermo sensitive male sterility has a great potential for hybrid production in wheat (Triticum aestivum L.). 337S is a novel wheat male sterile line sensitive to both short daylength/low temperature and long daylength/high temperature. Five F(2) populations derived from the crosses between 337S and five common wheat varieties were developed for genetic analysis. All F(1)'s were highly fertile while segregation occurred in the F(2) populations with a rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Further studies have proven that 337S is a male sterile line that is sensitive to both long day-length/high temperature and short day-length/low temperature condition, but it is fertile at normal planting time. These characteristics indicated that the fertility change of 337S line is due to the thermo-light condition of its cultivated environment, and 337S is a novel bi-pole-photo-thermo-sensitive genic male sterile (BP-PTGMS) line in wheat as described previously [ 19 , 20 ]. In order to explore the mechanism of male sterility in 337S line at short day-length/low temperature condition, we characterized the roles of miRNAs and their targets in BP-PTGMS of wheat, using high-throughput small RNA and degradome sequencing analyses.…”
Section: Introductionmentioning
confidence: 78%
“…Further studies have proven that 337S is a male sterile line that is sensitive to both long day-length/high temperature and short day-length/low temperature condition, but it is fertile at normal planting time. These characteristics indicated that the fertility change of 337S line is due to the thermo-light condition of its cultivated environment, and 337S is a novel bi-pole-photo-thermo-sensitive genic male sterile (BP-PTGMS) line in wheat as described previously [ 19 , 20 ]. In order to explore the mechanism of male sterility in 337S line at short day-length/low temperature condition, we characterized the roles of miRNAs and their targets in BP-PTGMS of wheat, using high-throughput small RNA and degradome sequencing analyses.…”
Section: Introductionmentioning
confidence: 78%
“…By virtue of their reproducibility, multi-allelic nature, co-dominant inheritance, relative abundance, and good genome coverage (Powell et al, 1996), SSR markers have been largely applied to genetic diversity studies (Gupta and Varshney, 2000;Chen et al, 2011;Zhang et al, 2013) and used in a variety of applications related to pears, demonstrating their adaptability for Pyrus (Yamamoto et al, 2002;Bao et al, 2007;Katayama et al, 2007;Yao et al, 2010;Cao et al, 2012). SSR loci consist of randomly repeated DNA regions with motif lengths of one to six base pairs (bp) and are spread throughout the genome (Tóth et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the published studies, 62,63 if the correlation coefficient between the element factors is positive, these factors may have a common source, mutual dependence, and identical behaviour during the transport. 64 Specifically, the highly significant positive correlations observed between these elements in river monitoring results may reveal multifaceted environmental dynamics and material behavior. Such positive correlations may reflect several aspects.…”
Section: Health Risks For Exposure To the Dtesmentioning
confidence: 99%